Overview of Photovoltaic Thermal (PVT) Water Collector - Ahmad Fudholi; Nur Farhana Mohd Razali; Abrar Ridwan; Rado Yendra; Hartono Hartono; Ari Pani Desvina; Majid Khan Bin Majahar Ali; Kamaruzzaman Sopian (Institute of Advanced Engineering and Science, 2018)
The popular solar technology is the integration of solar thermal technology and photovoltaic (PV), called photovoltaic thermal (PVT) technology. This technology converts solar energy to electrical and thermal energy. The efficiency of solar energy conversion via PVT is higher than photovoltaic and solar systems. PV cell efficiency decreases if system operating temperature is higher. Therefore, solar systems attached to PV cells act to cool PV cells and increase the overall efficiency of the PVT system. PVT construction that saves space, is suitable for domestic consumption, and long-term saving costs makes PVT current research by researchers in the latest energy technology. This review presents descriptions and previous works conducted on performances analysis of PVT water collector. Results on the performances of PVT water collectors are summarized. The energy and exergy efficiency of PVT water collector ranges from 28.5% to 85% and 6.8% to 14%, respectively.